Towards a Formal Definition of Active and Inactive Seafloor Massive Sulfide Deposits - J. W. Jamieson (International Marine Minerals Society, 2018)
INTRODUCTION Hydrothermal vents that form seafloor massive sulfide (SMS) deposits represent unique biodiversity hotspots that host many species that are found only at these sites. The destruction of these habitats remains one of the greatest environmental risks associated with proposed mining of SMS deposits. For this reason, there is a growing movement to protect active vent sites from direct and indirect effects of seafloor mining (Van Dover et al., 2018). Mitigating the adverse effects of mining on these ecosystems may prove to be one of the greatest challenges facing the marine minerals industry. At the same time, there is increasing evidence that inactive or extinct hydrothermal systems, which do not host the density or diversity of animals typical of active vents, may constitute a significant proportion of the SMS resource potential on the seafloor. Mining inactive SMS deposits may therefore present an extractive opportunity that does not necessitate the disturbance or destruction of active vent habitats. However, if mining of SMS deposits is to take place only at inactive vent sites in order to protect active vent ecosystems, a clear definition of what defines a site as active or inactive is necessary. ACTIVE AND INACTIVE SEAFLOOR MASSIVE SULFIDE DEPOSITS Our understanding of the number of inactive deposits, their size and grades, and how they are preserved on the seafloor remains limited, largely due to the challenges associated with finding these deposits. Over 90% of all hydrothermal vent fields discovered so far are hydrothermally-active. Almost all of these sites were discovered through the detection of chemical anomalies associated with active hydrothermal venting via water column surveys. Inactive sites have no associated hydrothermal plume, and thus the well- established plume survey exploration method is not effective. As a result, very few truly inactive sites inactive sites have been discovered. Alternative exploration methods, such as spontaneous potential (SP) surveys, magnetic surveys, and high-resolution mapping are required (Cherkashev et al., 2013; Jamieson et al., 2014; Tivey and Johnson, 2002). As methods for locating inactive deposits continue to develop, our understanding of the distribution and resource potential of these deposits will increase, and the focus of resource exploration will shift from active to inactive vent sites. However, for now, most exploration and deposit development activities remain focused on active vent fields.